2019
DOI: 10.15171/jcvtr.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

The value of negative stress echocardiography in predicting cardiovascular events among adults with no known coronary disease

Abstract: Introduction: Stress echocardiography is a safe and cost-effective method of evaluating the patients with suspected coronary artery disease (CAD). However, the risk factors of an adverse cardiovascular event after a normal exercise (ESE) or dobutamine (DSE) stress echocardiography are not well established. Methods: A cohort of 705 patients without previous history of CAD and a negative ESE/DSE was studied. All studies were performed in a high-volume echocardiologic laboratory and interpreted by two experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Of the patients who were indicated for revascularization but were not detected in the stress echo test due to a failure to achieve the target heart rate, eight out of nine of these patients had at least one of the following medical conditions: hypertension, diabetes, and/or known ischemic heart disease. This is in accordance with the study by Niloufar Samiei et al [13], who found that in patients with a negative stress test result or from dobutamine echocardiographic studies MACE occurred more frequently among older (≥65 years) men with preexisting diabetes, hypertension, and/or hyperlipidemia. Most of these patients underwent the SE during hospitalization for chest pain.…”
Section: Discussionsupporting
confidence: 92%
“…Of the patients who were indicated for revascularization but were not detected in the stress echo test due to a failure to achieve the target heart rate, eight out of nine of these patients had at least one of the following medical conditions: hypertension, diabetes, and/or known ischemic heart disease. This is in accordance with the study by Niloufar Samiei et al [13], who found that in patients with a negative stress test result or from dobutamine echocardiographic studies MACE occurred more frequently among older (≥65 years) men with preexisting diabetes, hypertension, and/or hyperlipidemia. Most of these patients underwent the SE during hospitalization for chest pain.…”
Section: Discussionsupporting
confidence: 92%
“…Under resting condition, MetS NHPs showed mild left ventricular (LV) diastolic dysfunction (E/A: 1+0.06 vs. 1.5+0. 13), but with preserved ejection fraction (EF: 65+2 vs. 71+3%) compared to CTRL. DSE with an intravenous infusion of dobutamine at ascending doses (5, 10, 20, 30 and 40 μg/kg/min, 7 min for each dose) resulted in a dose-dependent increase in cardiac function, however, with a signi cantly diminished magnitude at the highest dose of dobutamine infusion (40 μg/kg/min) in both diastole (E/A: -12+3 vs. -38+5%) and systole (EF: 25+3 vs. 33+5%) as well as ~42% reduced cardiac output reserve (COR: 63+8 vs. 105+18%, p<0.02) in the MetS compared to CTRL NHPs.…”
Section: Methods and Resultsmentioning
confidence: 96%
“…Clinical studies are now available re ning the common use of DSE preoperatively in patients with valvar disease, as well as in emergency cardiac situations [9][10][11]. Recently available long-term results from several independent clinical trials, combined with image enhancements, have improved the ability to detect signs of subtle coronary artery disease and determine myocardial viability [12,13].…”
Section: Introductionmentioning
confidence: 99%